Impact of absorptive capacity and dominant logic on innovation performance of public sector organizations in Hefei (Anhui Province), China - Farhan Khan; Zhang Xuehe; Fouzia Atlas; Kashif Ullah Khan; Adnan Pitafi; Muhammad Usman Saleem (Management Science Letters, 2017)
Public organization’s performance depends on multiple aspects in which there are different polit-ical and public actors involved. In this study, we discuss the innovation performance of public organizations’ in Hefei (Anhui province), China. Our targeted group for this study were public sector employees at different levels within the organizations being considered. We checked the effect of absorptive capacity (ACAP), and dominant logic on public organization’s innovation performance. We found that absorptive capacity and dominant logic had a positive relation-ship with firms’ performance. Furthermore, these predictors were not only improving firm’s per-formance, but also bring innovation into the public organizations.